Seasonal Analysis of Planetary Boundary Layer and Turbulence in Warsaw, Poland Through Lidar and LES Simulations - Rayonil G. Carneiro; Maciej Karasewicz; Camilla K. Borges; Lucja Janicka; Dongxiang Wang; Gilberto Fisch; Iwona S. Stachlewska (Remote Sensing)
We analyzed the planetary boundary layer (PBL) characteristics in Warsaw, Poland for a day of summer, autumn, winter, and spring of 2021 by integrating and comparing measured and simulated data. Using remote sensing lidar sensor data, the PBLH was calculated using wavelet covariance transform (WCT) and the gradient method (GM). Also, simulations of turbulent fluxes were performed utilizing the large eddy simulation (LES) from the Parallel Large Eddy Simulation Model (PALM) to better understand how turbulence and convection behave across different seasons in Warsaw. The PBLH diurnal cycles showed pronounced changes in their vertical structure as a function of the season: the winter heights were shallow (~0.7 km), while summer heights were deeper (~1.7 km). The spring and autumn presented transient characteristics of PBLH around 1.0 km. This study is crucial for enhancing urban air quality and climate modeling. The PBLH simulations from PALM showed agreement with the measured data, with an underestimation of approximately 10% in both methods. Through PALM, it was possible to observe that summer exhibited increased convection, enhanced mixing efficiency, and a deeper boundary layer compared to other seasons throughout the daily cycle. Winter has a lower sensible heat flux and little convection throughout the day. Spring and autumn showed intermediate characteristics. In this way, the effectiveness of the applicability of the PALM model to obtain flows within the PBL and their heights is highlighted, because correlations ranged from strong to very strong (r ≥ 0.70).